APLIKASI CARA VOLTAMETRI PELEPASAN ANOOIK UNTUK ANALISIS LOGAM BERAT OALAM PARTIKULAT OARI UOARA - Evita Boes (Jurnal Kimia Terapan Indonesia, 1991)
Determination of heavy metals such as Cu, Pb, Cd and Zn in airparticulate samples have been conducted by using Anodic Stripping Voltammerry method (ASV). Flow injection and wall-jet detector were supplemented to the ASV to improve the sensitivity and reproducibility of the mercury-film electrodes used. The air particulate samples analysed were taken with flow rate of 1 m3/minute. From 5 different places, 20 air samples were analysed and concentration of Cu, Pb, Cd; Zn between 0.0486-16.660 #gjm3 in airparticulates were observed. Limit of detection of the method for Cu, Pb, Cd and Zn were 0.015; 0.020; 0.016; 0.03 ppb respectively. Calibration curves for each metal from 50-500 ppb were linear with correlation coefficient 0.98.